2020
DOI: 10.3892/ijmm.2020.4827
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA NEAT1 ameliorates LPS‑induced inflammation in MG63 cells by activating autophagy and suppressing the NLRP3 inflammasome

Abstract: The mechanisms of inflammation in bone and joint tissue are complex and involve long non-coding RNAs (lncRNAs), which play an important role in this process. The aim of the present study was to screen out differentially expressed genes in human osteoblasts stimulated by inflammation, and to further explore the mechanisms underlying inflammatory responses and the functional activity of human osteoblasts through bioinformatics methods and in vitro experiments. For this purpose, MG63 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 76 publications
3
24
0
Order By: Relevance
“…Currently, our understanding of SARS-CoV-2 processes is limited, and there are no particular biomarkers associated with SARS-CoV-2 diagnosis or therapy. Since selected cellular ncRNAs (miR-155-5p, 27 , 28 , 29 , 30 , 31 MALAT-1, 32 , 33 , 34 , 35 NEAT-1[ 20 , 36 , 37 ] and THRIL[ 38 , 39 ]) may play critical roles in immune response regulation and inflammation, we evaluated the expression pattern of lncRNAs (MALAT-1, NEAT-1 and THRIL) and miR-155-5p in Peripheral Blood Mononuclear Cells (PBMC) of SARS-CoV-2 infected individuals in both acute and post-acute stages and compared to healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, our understanding of SARS-CoV-2 processes is limited, and there are no particular biomarkers associated with SARS-CoV-2 diagnosis or therapy. Since selected cellular ncRNAs (miR-155-5p, 27 , 28 , 29 , 30 , 31 MALAT-1, 32 , 33 , 34 , 35 NEAT-1[ 20 , 36 , 37 ] and THRIL[ 38 , 39 ]) may play critical roles in immune response regulation and inflammation, we evaluated the expression pattern of lncRNAs (MALAT-1, NEAT-1 and THRIL) and miR-155-5p in Peripheral Blood Mononuclear Cells (PBMC) of SARS-CoV-2 infected individuals in both acute and post-acute stages and compared to healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cells will switch to an autophagy pathway when apoptosis is inhibited (Yu et al 2021). It was previously reported that autophagy and apoptosis were closely associated with the differentiation of osteoblasts (Dai et al 2021). Moreover, mitogen-activated protein kinase (MAPK) could regulate cell proliferation, apoptosis and differentiation (Johnson and Lapadat 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that NEAT1 is involved in the regulation of autophagy. NEAT1 accelerates lipopolysaccharide-induced autophagy to enhance the inflammatory response in renal fibroblast cells and osteoblast cells [ 40 , 41 ]. Conversely, NEAT1 inhibits PTEN-induced kinase 1dependent autophagy by facilitating the proteasomal degradation of NEDD4-like E3 ubiquitin-protein ligase.…”
Section: Discussionmentioning
confidence: 99%